2010
DOI: 10.1371/journal.pone.0015588
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Sorafenib in Metastatic Melanoma with Tissue Correlates

Abstract: BackgroundSorafenib monotherapy in patients with metastatic melanoma was explored in this multi-institutional phase II study. In correlative studies the impact of sorafenib on cyclin D1 and Ki67 was assessed.Methodology/Principal FindingsThirty-six patients treatment-naïve advanced melanoma patients received sorafenib 400 mg p.o. twice daily continuously. Tumor BRAFV600E mutational status was determined by routine DNA sequencing and mutation-specific PCR (MSPCR). Immunohistochemistry (IHC) staining for cyclin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 33 publications
(43 reference statements)
2
62
0
Order By: Relevance
“…30,35 In clinical trials with advanced melanoma patients, sorafenib showed no clinical benefit as a single agent. 36,37 In the context of evaluating combination therapies, Flaherty et al presented encouraging preliminary results of sorafenib combined with carboplatin and paclitaxel (CP). 38 The combination showed a 37% partial response (PR) rate in the interim analysis while another 48% demonstrated stable disease (SD).…”
Section: Sorafenibmentioning
confidence: 99%
See 1 more Smart Citation
“…30,35 In clinical trials with advanced melanoma patients, sorafenib showed no clinical benefit as a single agent. 36,37 In the context of evaluating combination therapies, Flaherty et al presented encouraging preliminary results of sorafenib combined with carboplatin and paclitaxel (CP). 38 The combination showed a 37% partial response (PR) rate in the interim analysis while another 48% demonstrated stable disease (SD).…”
Section: Sorafenibmentioning
confidence: 99%
“…47 The most commonly observed drug-related AEs under sorafenib monotherapy were skin reactions (rash and palmarplantar erythrodysesthesia syndrome), gastrointestinal and constitutional disorders (corresponding grade 1e2 intensity). 36,37 Combination treatments with sorafenib led to hematotoxicity, fatigue, sensory neuropathy and skin reactions. 39,40,43 Based on the limited activity of sorafenib, doubts were raised concerning the potential of RAF inhibition as a therapeutic option.…”
Section: Sorafenibmentioning
confidence: 99%
“…It has however been noted that dasatinib was more effective than imatinib at reducing the viability of melanoma cells in two melanoma patients harboring the KIT L576P mutation which is the most frequent KIT mutation occurring in approximately 30%-40% cases of melanoma [44] . Furthermore, the data from a multi-institutional phase II trial with an oral multikinase inhibitor termed sorafenib, which targets different tyrosine protein kinases, including wild-type and mutant B-Raf and C-Raf kinases, PDGFRs, KIT, VEGFR2 and VEGFR3, performed with 36 patients with advanced melanomas have indicated that 1 patient showed a partial response for 175 d and 3 patients had stable disease with a mean duration of 37 wk [125] .…”
Section: Molecular Targeting Strategiesmentioning
confidence: 99%
“…These findings reveal a complex, interlinked network of cellular signaling pathways that contain several potentially synergistic therapeutic targets for metastatic melanoma. (Eisen et al 2006;Ott et al 2010), its use in combination with dacarbazine or temozolomide led to superior objective responses and progression -free survival compared to historical response rates to these agents (Amaravadi et al 2009). However, in a phase III randomized trial (E2603) comparing carboplatin, paclitaxel and sorafenib versus carboplatin, paclitaxel and placebo in chemotherapy-naïve patients, the futility analysis demonstrated no benefit of the three drug combination compared to the two drug chemotherapy combination.…”
Section: Agents Targeting Oncogenic Signaling Pathwaysmentioning
confidence: 99%